Arthroscopic repair of rotator cuff tears: analysis and functional outcome - Jacob, Rejo V.; Girotra, Prateek; Prashanth Kumar, K. (International Journal of Research in Orthopaedics, 2020)
Background: Rotator cuff injuries are common injuries occurring around the shoulder with an incidence ranging from 5 to 39%. Rotator cuff tears can be either partial thickness or full thickness. If remains untreated, may lead to persistent shoulder pain, functional limitation and decreased quality of life. In the present study, we assess the functional outcome following arthroscopic repair of rotator cuff tears. We also assess the various parameters affecting the functional outcome following repair. Methods: 15 patients with rotator cuff tears were subjected to this study. Preoperative evaluation of the American Shoulder and Elbow Surgeons (ASES) shoulder score and University of California and Los Angeles (UCLA) shoulder score was done. Arthroscopic rotator cuff repair using single row repair with suture anchors was done. The patients were followed up at 6 weeks, 3 months and 6 months where ASES score and UCLA score were assessed. Results: Of the 15 patients, 14 had supraspinatus tear, 2 patients had infraspinatus tear and 2 patients had subscapularis tear. According to UCLA scoring system 22% patients had excellent, 43% patients had good results, 23% patients had fair results and 12% patients had poor results. ASES score also showed progressive improvement at subsequent follow ups at 3 and 6 months. Conclusions: From our present study we conclude that arthroscopic rotator cuff repair is a good modality showing excellent functional outcome with less morbidity, minimal postoperative pain, better cosmesis and early resumption of daily routine activities.